European hot and dry summers are projected to become more frequent and expand northwards - Elizaveta Felsche; Andrea Böhnisch; Benjamin Poschlod; Ralf Ludwig (Communications Earth & Environment, 2024)
Abstract Heatwaves and dry spells are major climate hazards with far-reaching implications for health, economy, agriculture, and ecosystems. The frequency of compound hot and dry summers in Europe has risen in recent years. Here we present an examination of past extreme summers and compare them to future climate conditions. We use reanalysis data (2001–2022) and model data at three global warming levels: +1.2 °C, +2 °C, and +3 °C for nine selected sub-regions. Key findings indicate a significant increase in the frequency of most extreme past occurrences under 2 °C and 3 °C warming scenarios. For specific summers, the occurrence probability rises by up to 5–6 times from 2 °C to 3 °C. Moreover, our analysis reveals a notable northward shift in the climatology of hot and dry summers under 3 °C warming. The hot and dry climate observed in Eastern Europe under current conditions is anticipated to extend into substantial parts of the Baltic coast, Finland, and Scandinavia.